MELEURA BEACH TOURISM POTENTIAL AS A TOURISM OBJECT IN LAKARINTA VILLAGE, LOHIA DISTRICT, MUNA REGENCY, SOUTHEAST SULAWESI, INDONESIA - Wa Ode Mugini; Nasarudin Nasarudin; Gaby Kharisma (USN Kolaka, 2022)
Melura Beach tourism object has the potential to be developed into a tourist attraction as an educational tourism object. This study aims to 1) identify the tourism potential of Meleura Beach as tourism education in Lakarinta Village, Lohia District, Muna Regency. This research uses descriptive quantitative research method with data collection conducted in coastal areas by means of purposive sampling. The data analysis technique used in this study is the Tourism Suitability Index. The results of this study indicate the potential that can be developed, among others: the tourism potential of Meleura Beach consists of natural tourism in the form o, scenery, and tourist rides. This potential is very strategically located because it is casy to earch. Meleura Beach has a very interesting atmosphere. This is based on natural beach conditions, meaning that the water is clear and the rocks around it add to the beauty of the beach. Meleura beach has potential that can be developed, including the potential for natural resources, especially in terms of tourism and the potential for tourist attraction. The Meleura Beach area is very suitable to be used as a beach recreation tourism category with a tourism sutability index value at stations I,II, and III respectively 87%, 83%, and 71%. Based on the tourism suitability index matrix at stations I and II meleura beach is in the S1 category (Very Suitable), while station III is in the S2 category (appropriate). Meleura Beach has the potential to be used as an educational tourist attraction, where visitors who come not only for tours but visitors can get new knowledge about rocks. This potential can also be used for the world of education where students can directly study the rocks in Meleura Beach so that students get quality knowledge.